ANALYSIS OF INCOME RECOGNITION METHODS - Maizur Maharani Putri; Haliah; Nirwana (CV. Radja Publika, 2024)
The main problem that usually arises in revenue accounting is when revenue is recognized and measured, whether the revenue has been measured and recognized in accordance with generally accepted financial accounting standards. Because revenue recognition needs to be done at the right time for economic events that generate revenue, the amount recognized must also be measured precisely and precisely so that the company can present financial statements fairly. This research is in qualitative form, so the data taken is descriptive in the form of written or spoken words obtained from interviews, field notes and other materials so that it can be easily understood and informed by others. This research aims to determine the revenue recognition method used at PT. Indonesian Credit Insurance Makassar Branch. The research results show that revenue recognition at PT. Indonesian Credit Insurance Makassar Branch is carried out when the policy is issued and the Principal makes payment at the finance/cashier section with payment and is made if the Insured pays the premium in full to PT. Indonesian Credit Insurance Makassar Branch.